Evaluation of Coagulation Profile and Transfusion Support in Pre-eclampsia Patients: A Cross-sectional Study - Sivaranjani Vijayasundaram; Kavitha Govindasamy; Anitha Thayanidhi; Arumugam Pothipillai (Journal of Clinical and Diagnostic Research)
Introduction: Pre-eclampsia (PE) is an obstetric disorder characterised by high morbidity and mortality rates, yet it lacks a definitive etiology. The PE syndrome involves platelet activation, dysfunction and increased adherence, along with microangiopathic haemolysis. Consequently, coagulation and fibrinolytic status serve as good predictors for the onset and clinical severity of PE. Anticipating these coagulation disturbances in patients with PE can help prevent significant maternal morbidity and mortality. The need for blood components in PE typically arises in cases of thrombocytopenia and platelet dysfunction at the time of caesarean delivery, concomitant placental abruption, acute fatty liver disease, or dilutional coagulopathy resulting from major haemorrhage. Aim: To evaluate the coagulation profile and transfusion support in patients with PE. Materials and Methods: A prospective cross-sectional study was conducted at the Department of Transfusion Medicine, Institute of Obstetrics and Gynaecology (IOG), Chennai, Tamil Nadu, India, over a period of one year, from August 2017 to July 2018. The study included 30 normotensive pregnant women as controls (Group 1) and 50 pregnant women with PE as cases (Group 2). The cases were categorised as PE with severe features (n=22) and PE without severe features (n=28), according to American College of Obstetricians and Gynecologists (ACOG) Guidelines on Hypertension in Pregnancy. The platelet indices and coagulation parameters of the PE cases were compared with those of the normotensive pregnant women, as there is no standard reference available for our normotensive pregnant population. These parameters were observed initially at mid-pregnancy (24 to 27 weeks) and at late pregnancy (37 to 40 weeks) or at the time of admission for delivery, whichever was earlier, in both cases and controls. The collected data were analysed using IBM Statistical Package for Social Sciences (SPSS) Statistics software version 23.0. Results: The mean values of Platelet Count (PLC), Mean Platelet Volume (MPV) and Platelet Distribution Width (PDW) in late pregnancy for normal pregnant women (n=30) were 289.6±79.56, 10.12±0.83 and 13.28±1.78, respectively. The mean values of PLC, MPV and PDW in late pregnancy for PE cases with severe features were 184.05±74.08, 11.65±1.44 and 15.14±2.06, respectively. Statistical significance was obtained for PLC, MPV and PDW between the normal pregnant group (n=30) and the PE with severe features group (n=22), with p-values of less than 0.001, 0.0001 and 0.006, respectively. The mean values of Activated Partial Thromboplastin Time (APTT), Thromboplastin Time (TT) and Serum Fibrinogen (SF) in normal pregnancy were 24.6±7.5, 13.08±1.24 and 349.47±102.94, respectively. The mean values of APTT, TT and Serum fibrinogen for PE with severe features were 32.15±9.6, 14.74±1.15 and 235.09±76.52, respectively. There was a significant prolongation of APTT and TT, along with a significant decrease in Serum fibrinogen in PE with severe features when compared to the controls, with p-values of 0.001, 0.000 and 0.000, respectively. Conclusion: The evaluation of the coagulation profile in PE patients revealed a significant association between altered coagulation profiles and the severity of PE cases in late pregnancy. However, these parameters can only serve as indirect predictors, alongside the severity of symptoms of PE, in determining the need for prophylactic transfusion support.